Illness Perception and Its Association with Anxiety Among Hypertensive Outpatients - Ari, Elizabeth; Sinaga, Friska; Triastuti, Lidwina (Griya Eka Sejahtera, 2025)
Background: Hypertension is a major chronic condition that affects both physical and psychological health. Among hypertensive patients, anxiety is a common comorbidity that can interfere with disease management and quality of life. Illness perception, or how individuals interpret and respond emotionally to their condition, is thought to be a key factor influencing psychological outcomes. The aim of this study is to examine the association between illness perception and anxiety levels among hypertensive outpatients.Methods: This cross-sectional analytical study involved 130 hypertensive outpatients recruited through purposive sampling. Illness perception was assessed using the Brief Illness Perception Questionnaire (Brief IPQ), and anxiety was measured using the Zung Self-Rating Anxiety Scale (SAS). Pearson’s correlation test was used to analyze the relationship between the two variables.Results: The mean illness perception score was 53.1 (SD = 10.7), while the mean anxiety score was mild to moderate. A moderate, statistically significant positive correlation was found between illness perception and anxiety (r = 0.482, p < 0.001). Patients who perceived their hypertension as more threatening and uncontrollable reported higher levels of anxiety.Conclusion: Negative illness perceptions are significantly associated with increased anxiety among hypertensive outpatients. Routine hypertension management should incorporate strategies to assess and address patients' beliefs and emotional responses toward their illness to support better psychological and clinical outcomes